About the survey - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Part of being a publication is to keep up a good relationship with the readers. Every successful magazine, whether it is a local newsletter, a scientific journal or an international weekly, has its own ways of keeping in touch with readers: a...